Assessing Pyrolysis for Bio-diesel and Energy Generation from Diverse Municipal Solid Waste with Environmental Impact Analysis - Mohsin Arbab; Muhammad Salman Abbasi (Spectrum of Engineering Sciences, 2025)
Conversion of municipal solid waste (MSW) to energy through the pyrolysis process is a sustainable waste management system. For the pyrolysis process, a reactor was designed and manufactured on the principles of the thermal pyrolysis process to recycle the plastics, wood and refuse-derived fuel (RDF) into biodiesel. Municipal solid waste was divided into two groups (1) Wood, RDF and a mixture of wood and RDF (2) different types of plastics. The thermal pyrolysis reactor in this study made bio-diesel from plastics, wood, and RDF. Both wood, RDF, and a combination of both, and polymers were employed. Though energy-rich, RDF produced just 4.4% bio-diesel while wood produced 15.56%. PP produced the most biodiesel at 67.8%, followed by HDPE at 54.4%, PET at 43.8%, and mixed plastics at 16.5%. Biodiesel feedstocks vary substantially in calorific value. Biodiesel from wood had 9.6 MJ/kg in the first group, but RDF had 28.05 MJ/kg, showing its energy output potential despite its lower yield. In the second group, PP had the highest calorific value at 30.42 MJ/kg, followed by HDPE at 28.09, PET at 19.86, and mixed plastics at 16.5. PP and HDPE make bio-diesel more efficiently than wood. The feedstock strongly impacts pyrolysis' environmental impact, especially CO2 emissions. Wood pyrolysis produced bio-diesel with 104.8 g of CO2 per kg, cleaner than RDF at 379.8 g. Sustainable energy generation is better with PP and HDPE than RDF since they produce less CO2. These findings suggest investigating alternative pyrolysis procedures to improve bio-diesel yield and reduce environmental impacts, particularly greenhouse gas emissions, for a more sustainable waste-to-energy conversion process.